2005
DOI: 10.1111/j.0030-1299.2005.13911.x
|View full text |Cite
|
Sign up to set email alerts
|

How to predict attachment potential of seeds to sheep and cattle coat from simple morphological seed traits

Abstract: P. 2005. How to predict attachment potential of seeds to sheep and cattle coat from simple morphological seed traits. Á/ Oikos 110: 219 Á/230.Dispersal is a process that determines many aspects in the life-history of plants. Up to now, however, it is difficult to quantify. Many studies rather assess it as a categorical trait, i.e. assuming a species is dispersed by a certain vector or not. Gradual differences in the dispersal potential between species are rarely considered.In this paper we focus on the key pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
147
0
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(160 citation statements)
references
References 45 publications
(58 reference statements)
4
147
0
9
Order By: Relevance
“…On the basis of results of performed studies and published data (Graae 2002;Römermann et al 2005), it can be concluded, that an increase in the stem length, fruit and seed production, as well as in seed dimensions and considerable seedling emergence enable persistence of Bidens frondosa population in open and sun-lit sites. Simultaneously, it should be add that a decrease in the height of the stems and achene size in partly-shaded and shaded places might contribute to long-distance dispersal of seeds by animals, while the substantial seedling recruitment allows to successful colonization of new areas.…”
Section: Bidens Frondosamentioning
confidence: 96%
“…On the basis of results of performed studies and published data (Graae 2002;Römermann et al 2005), it can be concluded, that an increase in the stem length, fruit and seed production, as well as in seed dimensions and considerable seedling emergence enable persistence of Bidens frondosa population in open and sun-lit sites. Simultaneously, it should be add that a decrease in the height of the stems and achene size in partly-shaded and shaded places might contribute to long-distance dispersal of seeds by animals, while the substantial seedling recruitment allows to successful colonization of new areas.…”
Section: Bidens Frondosamentioning
confidence: 96%
“…More on methods: Fischer et al (1996); Römermann et al (2005aRömermann et al ( , 2005bRömermann et al ( , 2005c.…”
Section: Special Cases or Extrasmentioning
confidence: 99%
“…Both seed mass and seed morphology were positively correlated (on 130 species tested) with attachment potential in a model [25]. The "retention potential" of seeds has also been experimentally tested in 100 species [44].…”
Section: Discussionmentioning
confidence: 96%
“…Sheep epizoochory is an important dispersal factor that also has implications for grassland conservation and restoration [1,25,44,56]. The long-distance dispersal potential of species within the present-day communities is positively associated with the amount of grassland in the historical landscape and with the continuity of grazing management [57].…”
Section: Comparison Of the Sampling Methodsmentioning
confidence: 99%
See 1 more Smart Citation